Current anti-copper therapies in management of Wilson disease - Mohr, Isabelle; Weiss, Karl Heinz (Annals of translational medicine, 2019)
In Wilson disease (WD) severity of disease can vary widely, depending on time of diagnosis. Early treatment can prevent the development of symptoms in patients. In all patients, lifelong medical treatment is indicated. Currently available medical regimens include the copper chelators for example D-penicillamine (DPA) or trientine (TETA), acting to increase copper excretion and zinc salts (ZS), which reduce copper uptake. In this chapter, we discuss considerations regarding choice of drug and safety limitations.
Gesehen am 21.10.2019